Materialitas : working stone, carving identity - O'Connor, Blaze; Cooney, Gabriel; Chapman, John, 1951- (Prehistoric Society research paper, 2010)
"Stone monuments and objects are highly accessible today and formed a focus for engagement, transformation and re-use in the past. Stone is inextricably linked to ideas of monumentality and remembrance. It formed an active medium in the creation of identities and memory in a range of social contexts and practices, including the embodied, performative and incorporated practices of daily activities and traditions. It can be argued that the material presence and physical character of stone objects and monuments were not only actively harnessed in these encounters, but were also the very stuff from which social relations were derived, perceived and thought through. This volume explores the power and effect of stone through the meanings that emerged out of people's engagement and encounters with its physical properties. Focused primarily on the Neolithic and Bronze Age of Atlantic Europe it brings together authors working on the materiality (materialitas) of stone via stone objects, rock art, monuments and quarrying activity. This highlights the connections that cross-cut what are traditionally seen as disparate research areas within the archaeological discipline."--Back cover